Method validation for determination of sucralose in beverage by high performance liquid chromatography - Jitkaew, Nantida; Sinaviwat, Savarin (Bulletin of Applied Sciences, 2022)
The determination of sucralose in beverages was performed and validated by the modified standard method based on BS EN 16155:2012 Foodstuffs - Determination of sucralose - High performance liquid chromatographic method. The linear calibration curve was obtained in concentrations ranging from 0 to 400 mg/L. The limit of detection (LOD) and the limit of quantitation (LOQ) were 4.0 and 15.0 mg/kg, respectively. The precision and accuracy studies were performed by spiking 3 concentration levels in the samples (25, 250, and 2,000 mg/kg). The recoveries were obtained from 92.0 to 101.6%, 98.8 to 99.4% and 98.0 to 99.8%, respectively. The precision calculated as a relative standard deviation of repeatability (%RSDr) found good repeatability at 3.799%, 0.169%, and 0.586%. The HORRAT values were 0.824, 0.052 and 0.246, respectively. The percent recovery, precision, and HORRAT value were acceptable and complied with the requirement of EURACHEM/CITAC Guide: 2012. The percentage of expanded uncertainty was 3.7% at a 95% confidence interval (k=2). Moreover, thirty samples from local markets were analyzed following this validated method and found that sucralose concentration ranged from not detected or less than 4.0 to 172.7 mg/kg. The result of this study showed the modified methods were fit for the intended use.